2010
DOI: 10.1088/0004-637x/720/2/1674
|View full text |Cite
|
Sign up to set email alerts
|

Photometric Properties of the M33 Star Cluster System

Abstract: We present a catalog of 2990 extended sources in a 1• × 1 • area centered on M33 using the MegaCam camera on the 3.6 m Canada-France-Hawaii Telescope. The catalog includes 599 new candidate stellar clusters, 204 previously confirmed clusters, 1969 likely background galaxies, and 218 unknown extended objects. We present ugriz integrated magnitudes of the candidates and confirmed star clusters (SCs) as well as the full width at half maximum, ellipticity, and stellarity. Based on the properties of the confirmed S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 53 publications
(67 reference statements)
1
46
0
Order By: Relevance
“…We derive R e for these galaxies using catalogs in the published literature (Harris 1996;van den Bergh & Mackey 2004;Nantais & Huchra 2010;San Roman et al 2010;Caldwell et al 2011;Fan & de Grijs 2014). These measurements are uncertain due to the inhomogeneous coverage and depths of the various surveys, but a trend is apparent where metal-poor GC systems with more GCs have larger sizes.…”
Section: Ultra-diffuse Galaxies As "Pure Stellar Halos"mentioning
confidence: 99%
“…We derive R e for these galaxies using catalogs in the published literature (Harris 1996;van den Bergh & Mackey 2004;Nantais & Huchra 2010;San Roman et al 2010;Caldwell et al 2011;Fan & de Grijs 2014). These measurements are uncertain due to the inhomogeneous coverage and depths of the various surveys, but a trend is apparent where metal-poor GC systems with more GCs have larger sizes.…”
Section: Ultra-diffuse Galaxies As "Pure Stellar Halos"mentioning
confidence: 99%
“…Recently San Roman et al (2010) observed 803 M 33 star clusters (599 candidates and 204 confirmed using the HST) using the 3.6 m Canada-France-Hawaii-Telescope (CFHT) and published a catalog in the MegaCam camera u * g r i z photometric system. Although their catalog also contained the cluster photometry converted to the ugriz photometric system of the Sloan Digital Sky Survey (SDSS), we considered here the native MegaCam photometric system to avoid likely conversion approximation.…”
Section: The Cluster Datamentioning
confidence: 99%
“…To this end, we use three catalogs of clusters recently published in the literature: the San Roman et al (2010) catalog in the u * g r i z photometric system, and the Ma (2012Ma ( , 2013 and Fan & de Grijs (2014) catalogs in the standard UBVRI photometric system. We also use nearinfrared photometry that we derive from deep 2MASS images.…”
Section: Introductionmentioning
confidence: 99%
“…Although they are similar in appearance, M 33 has a disk break at ∼8 kpc (Ferguson et al 2007;Barker et al 2007Barker et al , 2011, while NGC 300 has a pure exponential disk out to ∼14 kpc (Bland-Hawthorn et al 2005). Furthermore, there is an HI bridge between M 33 and M 31 (Karachentsev et al 2004;Putman et al 2009), indicating the probability that they interacted with each other in the past (Braun & Thilker 2004;McConnachie et al 2010;San Roman et al 2010;Bernard et al 2012). This result is confirmed by the evidence for tidal disruption of M 33's gas disk (Rogstad et al 1976;Deul & van der Hulst 1987;Corbelli & Schneider 1997;Karachentsev et al 2004;Putman et al 2009).…”
Section: Introductionmentioning
confidence: 98%